Graph-Based Quantification of Basketball Spacing Using Spatial and Network Metrics - Tsiakalos, Apostolos; Tsiakalos, Anastasios (Stadium - Hungarian Journal of Sport Sciences, 2025)
In modern basketball, effective player spacing is critical for optimizing offensive efficiency and shot quality. This paper proposes a novel approach to quantifying spacing using graph theory. Each player is represented as a node, and the pairwise Euclidean distances between them form the weighted edges of a complete graph. We compute several spatial and structural metrics, including total spacing, convex hull area, minimum spanning tree weight, and centrality measures. Our method allows for a frame-by-frame quantitative analysis of spacing, revealing key patterns associated with successful possessions. Results demonstrate that certain geometric and network-derived properties are strong indicators of tactical efficiency.